A Marriage Made in Heaven The Sexual Politics of Hebrew and Yiddish. - Seidman, Naomi (Contraversions: Critical Studies in Jewish Literature, Culture, and Society Series., 2021)
With remarkably original formulations, Naomi Seidman examines the ways that Hebrew, the Holy Tongue, and Yiddish, the vernacular language of Ashkenazic Jews, came to represent the masculine and feminine faces, respectively, of Ashkenazic Jewish culture. Her sophisticated history is the first book-length exploration of the sexual politics underlying the ""marriage"" of Hebrew and Yiddish, and it has profound implications for understanding the centrality of lang.